Evaluation of the treatment of malignant melanoma: about 110 observations - Priario, Julio C; D'Auria, Agustín; Borges, Freddy; Favat, Juan; Lima, Fabio; Martínez de Lima, Gladys; Ramos, Sergio (Cirugía del Uruguay, 1973)
The paper contains an evaluation of the treatment applied in 110 cases of malign melanoma with a recovesy percentage of 17 .1 % , The best results were obtained throigh the association of surgery and chemiotherapy by perfusion, but this latter procedure is reserved for lesions in the limbs.